PENGARUH HIPNOTHERAPY TERHADAP KECANDUAN GAME ONLINE PADA REMAJA DI SMP NEGERI 1 CILEUNYI: Hipnotherapy, Kecanduan game online - Juhaeriah, Juju (JURNAL KESEHATAN KARTIKA, 2021)
Title : The Effect Of Hypnotherapy On Online Game Addiction On Adolescents At Smp Negeri 1 Cileunyi Background: Addiction to online games in adolescents can affect the social aspects of adolescents in living their daily social life. One result is that online gaming addicts will sit at the computer for hours playing online games and neglect other tasks. Generally addicts play online games more than 8-10 hours per day and at least 30 hours per week. The prevalence of mental emotional disorders as indicated by symptoms of depression and anxiety for ages 15 and over reaches around 14 million people or 6% of Indonesia's population, one of which is due to addiction to online games. According to Mental Health First Aid, help for mental health or early mental health support can be overcome by using hypnotherapy. Objectives: Knowing the effect of hypnotherapy on online game addiction in adolescents at SMP Negeri 1 Cileunyi. Methods: The research design used was pre-experiment with one group pretest postest design. the sample of the study was 32 class 1 adolescents with heavy online game addiction at SMPN 1 Cileunyi. The sampling technique was purposive sampling. The bivariate analysis used in this study used the Wilcoxon analysis. Results: Addiction to online games before being given hypnotherapy, namely the mean time to use online games before being given hypnotherapy of 240.00 minutes per day with a standard deviation of 7.36. Addiction to online games after being given hypnotherapy is an average usage time of 135.44 minutes per day with a standard deviation of 0.80. Conclusion: There is an effect of hypnotherapy on online game addiction in adolescents at SMP Negeri 1 Cileunyi with p.value is 0.000 ≤ alpha α (α = 0.05).